90 IMPACT OF AN INTEGRATED CARE MODEL FOR OLDER PERSONS: EVALUATING A PILOT PROGRAMME. (18th November 2021) - Geoghegan, J; Conry, M; Mannion, E; Shiel, E; Flanagan, L; McCleane, F; Nolan, M; Corry, M; Chawke, M; Coffey, K; Costello, M; McCarty, C E; et al.
Abstract: Background: In September 2019 Sláintecare helped establish an Integrated Care team for Older People. The aim of this service was to provide a Comprehensive Geriatric Assessment (CGA) to older people within a community network. Service user experience/feedback are critically important for development of a team and a service. To give service users a platform to evaluate the service a patient experience survey was conducted. Methods: The survey was designed by the multidisciplinary team, consisting of 13 closed/3 open questions. A Likert scale was utilised for closed questions and thematic analysis for open questions. A question on impact of COVID-19 was also included. 150 of the 950 service users who received a CGA from June 2020 to June 2021 were selected randomly and invited to participate in the postal survey. All participants received a covering letter, questionnaire and a stamped address envelope to return their completed surveys. Results: 47% response rate (71/150). 77% were aged ≥75. 52% completed the survey themselves, 48% required assistance. 61% attended more than twice and most would prefer to attend a local spoke clinic. 96% agreed/strongly agreed that they were satisfied with the service. 99% felt they were treated with dignity/respect and had confidence in the service. 93% agreed that they were involved in care decisions. 82% reported their carers had the opportunity to discuss concerns. Themes emerging included importance of care close to home, avoiding acute hospital, difficulty parking at tertiary centres. 42% highlighted isolation and loneliness due to COVID-19 as a major issue. Conclusion: Service users had an overwhelmingly positive experience especially when care was delivered in clinics close to their homes. Development of the hub and spoke model is acceptable and feasible to older people and their carers' in this region and will be the focus for expansion of this service.